APPROACH TO THE PRESENTATION OF INFORMATION IN TERMS OF THE SUBJECT FIELD - Ternovoy, M. Yu. (Radio Electronics, Computer Science, Control, 2024)
The approach to information obtaining from database and its representation in the terms of data domain was proposed. This approach is represented by the method of data domain binding and the method of query construction in data domain terms.